1999
DOI: 10.1016/s0954-6111(99)90266-4
|View full text |Cite
|
Sign up to set email alerts
|

Does the ‘Oxygen cost diagram’ reflect changes in six minute walking distance in follow up studies?

Abstract: The oxygen cost diagram (OCD) is a simple scale for quantifying a patient's evaluation of his tolerance to exercise frequently used in clinical trials; it has been shown to be well correlated with objective measures of capacity of ambulation such as the 6 min walk test (6' W). This study aimed to determine whether the OCD accurately depicts changes in capacity of ambulation either quantitatively or qualitatively. OCD ratings were analysed at baseline and after a 1 yr follow-up, in patients treated by non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The administration of the OCD is very rapid (takes about 1-2 minutes), and in patients with COPD the OCD has been found able to distinguish different levels of disease severity [53]. However, longitudinal studies testing the instrument's sensitivity with respect to variations in physical condition have shown a poor capacity of this scale to detect both improvement and decline post-rehabilitation [54,55]. …”
Section: Dyspnea Measurement In Daily Living Activitiesmentioning
confidence: 99%
“…The administration of the OCD is very rapid (takes about 1-2 minutes), and in patients with COPD the OCD has been found able to distinguish different levels of disease severity [53]. However, longitudinal studies testing the instrument's sensitivity with respect to variations in physical condition have shown a poor capacity of this scale to detect both improvement and decline post-rehabilitation [54,55]. …”
Section: Dyspnea Measurement In Daily Living Activitiesmentioning
confidence: 99%
“…Indeed, the impact of isolation and decreases in social interactions and relationships on morbidity and mortality has been documented in subjects with preexisting health conditions [29][30][31]. Although patients did mention social isolation as a problem, HAD scores were well within or below published values for patients under HMV, with a remarkably low prevalence of anxiety or depressive disorders in spite of the pandemic [27,[32][33][34][35][36][37]. Interestingly, a Spanish study which included 100 patients with COPD reported that patients' feelings regarding their lung disease and general health were similar or even better during lockdown [38].…”
Section: Discussionmentioning
confidence: 98%
“…The administration of the OCD is very rapid (takes about 1-2 minutes), and in patients with COPD the OCD has been found able to distinguish different levels of disease severity [53]. However, longitudinal studies testing the instrument's sensitivity with respect to variations in physical condition have shown a poor capacity of this scale to detect both improvement and decline post-rehabilitation [54,55].…”
Section: Absence Of Dyspneamentioning
confidence: 99%